Legal and Institutional Requirements For Trend towards Takaful in Algeria - Yacine, KHELOUF; Hocine, HASSANI (The Arab Journal of Administration, 2020)
The Algerian Insurance sector contributes to fulfilling the Economic development goals through the stakeholders’ collaboration in securing economic and social stability. The Algerian insurance sector is distinct from that of the neighbouring countries, through the domination of traditional insurance practices, and the newness of the «Takaful system», which is applied by Salam Company that adopts-as all the other Companies- a traditional insurance system. In this paper, we try to highlight the legal and institutional requirements to develop the Algerian Takaful Insurance Market, by identifying the status of Takaful in the world, and comparing the Algerian insurance market to other similar markets, with the purpose of suggesting the required modifications in the Algerian Insurance Law, with the focus on different accounting, legal, and technical aspects relevant to insurance activity.